THE USE OF PAYMENT SYSTEM (QRIS) ON UMKM BUSINESS DEVELOPMENT AT STIEM BONGAYA CAMPUS - Tenriola Tenriola; Dahniyar Daud; Angga Setiawan; Ahmad Duwaidar; Putri Pratiwi Amran (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2025)
Currently, QRIS has begun to be widely used by MSMEs as a more efficient non-cash payment system, but some parties have doubts about the security and effectiveness of this payment system. This study aims to determine how the QRIS Payment System affects MSME business development at the Stiem Bongaya Campus. In this study, the research method used was quantitative method, with data collection techniques through observation, questionnaires and documentation. The sample used is the sample formulated by Slovin, namely 100 Stiem Bongaya students. The data obtained from the research results and processed using data analysis and the help of the Microsoft Excel program and SPSS version26 which consists of validity and reliability tests, simple linear regression analysis and the coefficient of determination. The results of this study indicate that the perceived influence of the QRIS Payment System in Makassar City is in the good category with an achievement of 78.65% and MSME Business Development is also in the good category with an achievement of 77.25%. The QRIS Payment System variable has a positive and significant effect on the dependent variable MSME Business Development.